Stereochemistry of 2D Molecular Crystallization - Karl-Heinz Ernst (CHIMIA, 2014)
Different stereochemical aspects of molecular recognition in two-dimensional crystallization on metal surfaces are discussed. Scanning tunneling microscopy, a powerful tool with submolecular resolution capabilities, provides detailed insight into the implications of molecular geometry for the two-dimensional crystal lattice. The examples presented here include a homo- to heterochiral phase transition, tiling with pentagonal molecules, chiral restructuring of a metal surface and diastereomeric recognition between enantiomers of different molecular species via polar forces as well as van der Waals interactions.